Reallocation and productivity during commodity cycles - Rodrigo Heresi (Inter-American Development Bank (IDB), 2021)
I study the firm-level dynamic response of a commodity-exporting economy to global cycles in commodity prices. To do so, I develop a heterogeneous-firms model that endogenizes declines in aggregate productivity through reallocation towards less productive firms. Within a given sector, commodity booms reallocate market share away from exporters because of currency appreciation and away from capital-intensive firms because of the increase in capital cost. I provide empirical evidence for these channels using microdata for Chile, the worlds largest copper producer. When fed with the commodity super-cycle of 2003-2012, the calibrated model generates about 50% of the observed productivity decline.
Keywords: D24; Q33; F41; 330; Productivity; Resource booms; Open economy macroeconomics